2016
DOI: 10.1128/aem.03982-15
|View full text |Cite
|
Sign up to set email alerts
|

Soil Characteristics Driving Arbuscular Mycorrhizal Fungal Communities in Semiarid Mediterranean Soils

Abstract: We investigated communities of arbuscular mycorrhizal fungi (AMF) in the roots and the rhizosphere soil of Brachypodium retusum in six different natural soils under field conditions. We explored phylogenetic patterns of AMF composition using indicator species analyses to find AMF associated with a given habitat (root versus rhizosphere) or soil type. We tested whether the AMF characteristics of different habitats or contrasting soils were more closely related than expected by chance. Then we used principal-com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 89 publications
4
33
0
Order By: Relevance
“…Although the Northern, Brong-Ahafo, and Ashanti regions also showed high AP levels, under the agroecological zones, the GSZ was observed to possess the lowest level compared to the FSTZ and DFZ. In previous studies, it was demonstrated that the soil physiochemical properties affected the composition of AMF communities and influenced their distribution and performance in the agricultural environment [30,42,60,[75][76][77][78]. In the present study, the AMF communities based on the observed OTUs were affected independently by AP content and their interactions with other nitrogen source elements, such as NO 3 and C/N.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Although the Northern, Brong-Ahafo, and Ashanti regions also showed high AP levels, under the agroecological zones, the GSZ was observed to possess the lowest level compared to the FSTZ and DFZ. In previous studies, it was demonstrated that the soil physiochemical properties affected the composition of AMF communities and influenced their distribution and performance in the agricultural environment [30,42,60,[75][76][77][78]. In the present study, the AMF communities based on the observed OTUs were affected independently by AP content and their interactions with other nitrogen source elements, such as NO 3 and C/N.…”
Section: Discussionsupporting
confidence: 54%
“…In several studies, the occurrence of AMF colonization in rice roots under different production regimes at diverse geographical locations demonstrated variable effects on the community compositions of AMF [26,[41][42][43]. Lumini et al [44] reported that AMF colonization in rice roots occurred only under dry conditions and not in the conventional paddy wet fields.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have previously reported how environmental filtering, that is soil properties and climatic variables are strong predictors of the AM fungal community assembly in natural environments (Alguacil, Torres, Montesinos‐Navarro, & Roldán, ; Bouffaud et al, ; Lekberg et al, ; Rodríguez‐Echeverría et al, ; Vályi, Mardhiah, Rillig, & Hempel, ). Our results confirm that the abiotic environment undoubtedly plays a key role in abundance and distribution of this group of micro‐organisms in rain forests, but other drivers than the environment alone should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation with AMF would result in higher water availability due to the stronger water absorption of hypha and would make further efforts to restore the plant hydraulic status with higher soil drying rates [4,33,60]. Electrical conductivity, which has a positive correlation with soil moisture within a certain range, has also been found to have a clear correlation with AMF inoculation [63,64]. As for enzyme activities, though the impact mechanism is not yet clear, researchers have detected increases in β-glucosidase [63], catalase [45,63], urease [17], dehydrogenase [17], protease [17], peroxidas and dismutase [47], and phosphatase activities [17,63], and transient increases in catalase activity after AMF inoculation [17].…”
Section: Effects Of Amf On Soilmentioning
confidence: 99%
“…As for enzyme activities, though the impact mechanism is not yet clear, researchers have detected increases in β-glucosidase [63], catalase [45,63], urease [17], dehydrogenase [17], protease [17], peroxidas and dismutase [47], and phosphatase activities [17,63], and transient increases in catalase activity after AMF inoculation [17]. Studies also have shown a negative correlation between AMF and clay content [64], which may result in an increase in silt percentage. Those results may be due to more oxygen provided by soil with a high sand content, which can satisfy the oxygen requirement of AMF [65].…”
Section: Effects Of Amf On Soilmentioning
confidence: 99%